Prevalence of Multidrug resistant Staphylococcus Aureus isolates in Clinical specimens collected from local patients of Chittagong, Bangladesh (Chittagong University Journal of Biological Sciences, 2013)
To observe the prevalence of Staphylococcus aureus a total of 1078 blood, pus and miscellaneous samples (sputum, swab and body fluids) were collected among which 478 samples exhibited bacterial growth on agar medium. Out of growth positive 300 pus samples, 116(38.67%) showed the growth of Gram positive cocci, of which 30(25.86%) were Staphylococcus aureus positive. In case of blood, the number of growth positive samples were 116(28.45%), of which 33(12.12%) showed the presence of Gram positive cocci including 4 Staphylococcus aureus. Among the 62 growth positive miscellaneous samples, the number of Gram positive cocci and Staphylococcus aureus positive samples were 22(35.48%) and 4(18.18%), respectively. From the antibiogram of 38 Staphylococcus aureus isolates, 26 were found multidrug resistant, showing resistance against two or more of the antibiotics used namely ampicillin, cefradine, gentamicin and ciprofloxacin, whereas all the isolates were sensitive to vancomycin. The MIC and MBC of these antibiotics against different Staphylococcus aureus isolates were determined, which were found to range from 2?g/ml to 8?g/ml and 4?g/ml to 16?g/ml, respectively, in case of vancomycin. The rate of resistance against ampicillin, cefradine, gentamicin and ciprofloxacin were 92.1%, 60%, 58.1% and 59.35%, respectively. DOI: http://dx.doi.org/10.3329/cujbs.v6i1-2.17242 The Chittagong Univ. J. B. Sci.,Vol. 6(1&2):175-185, 2011